Thoughts of Jama’ah An-Nadhir About Philosophical and Methodological Studies in Determining the Beginning of the Hijri Month - Muhajir, Muhajir; Nugraheni, Puspa; Nabila, Putri Syasya (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Jama’ah An-Nadzir is a minority Islamic group that has different religious views and practices from the majority of Muslims in Indonesia. They claim to follow the original teachings of the Prophet Muhammad and have a unique method in determining the beginning of the Hijri month, especially in determining 1 Ramadan and 1 Shawwal. The process of determining the beginning of the month is done by observing natural phenomena, including sea tides and the moon’s circulation, which is different from the methods commonly used by other Islamic organizations. This paper highlights the importance of astrology in determining the time of worship, as well as how Jamaah An-Nadzir applies the istinbat method based on astronomical and mathematical observations. Thus, this study not only explains the religious practices of Jamaah An-Nadzir but also provides insight into the interaction between beliefs, scientific observations, and worship practices in the context of the Hijri calendar.